COMPARATIVE UTILIZATION OF SEWAGE SLUDGE, POULTRY DROPPINGS AND GROUNDNUT CAKE RATIONS BY WEST AFRICAN DWARF GOATS - OKAGBARE, G. O.; AKINSOYINU, A. O. (Nigerian Journal of Animal Production, 2021)
Eighteen young West African dwarf (WAD) goats were used to compare the utilization of sewage sludge, poultry dropping and groundnut cake rations by WAD goats. Total dry matter intake of the animals fed diet A (groundnut cake based ration) and C (poultry dropping based ration) was significantly (P < 0.05) higher than dry matter intake of animal fed diet B (dry activated sewage sludge based ration). Total dry matter intake of animal fed diet A (664.6 g/day) appeared to be higher than those fed diet C (600.5g/day), although the differences observed were and significant. Values observed for apparent dry matter, ether extract and nitrogen-free extract digestibilities between animals fed the different diets were not significant (P > 0.05). crude fibre and crude protein digestibility values however varied appreciably. Values recorded (12.03, 1.04 and 10.42 g/day and 3.13, 0.28 and 2.72 g.day/w 0.75kg for animals fed diets A, B, and C respectively) for nitrogen balance and weight gains (56.8, -2.7 and 36.8 g/day for animals fed diets A, B and C respectively) were higher for animals fed diet A, followed by animals fed diets C and B respectively.